It Was Trial by Fire: Recommendations for Building a Stronger Nursing Home Workforce After COVID-19. (17th December 2021) - Franzosa, Emily; Mak, Wingyun; Burack, Orah; Boockvar, Kenneth; Reinhardt, Joann
Abstract: The COVID-19 crisis showed the urgent need for a unified, well-supported nursing home workforce. The objective of this qualitative study was to examine the lived experience of certified nursing assistants (CNAs) and administrators during COVID-19 to identify best practices moving forward. Six administrator interviews and 10 remote focus groups with CNAs at 5 nursing homes (N=56) were examined through directed content analysis. Based on priorities identified by CNAs and administrators, the following practices may be most impactful: 1) ongoing and responsive staff training; 2) transparent, direct, and two-way communication channels; 3) prioritizing hiring permanent staff to avoid shortages and reliance on agency staff; 4) building collaborative staff-management relationships; 5) providing flexible job benefits; 6) providing staff-centered emotional support resources; and 7) appraising COVID-19 innovations. Our results suggest that rather than returning to "business as usual, " nursing homes can draw on these lessons to build a more sustainable workforce and industry.